Immune checkpoint inhibitor-induced subacute cutaneous lupus erythematosus: a case report and review of the literature - Khorasanchi, Adam; Korman, Abraham M.; Manne, Ashish; Meara, Alexa (Frontiers in Medicine, 2024)
Immune checkpoint inhibitor (ICI) use has been associated with numerous autoimmune side effects, known as immune related adverse events (irAEs). Cutaneous irAEs are common and affect up to 50% of patients treated with ICIs. There have been an increasing number of cases reported in the literature regarding ICI-induced subacute cutaneous lupus erythematosus (SCLE). ICI-induced SCLE is important to recognize as it can result in a delayed and/or prolonged skin reaction despite treatment discontinuation. We describe a patient with gastro-esophageal adenocarcinoma who developed SCLE following one cycle of nivolumab treatment. A 75-year-old man presented to our clinic with a new photo-distributed rash composed of oval scaly pink papules and plaques involving his chest and arms. Despite treatment with topical corticosteroids, he presented to the emergency department one week later with worsening rash. Skin biopsy showed vacuolar interface pattern, along with superficial perivascular lymphocytic infiltrate, consistent with a drug eruption. The clinicopathological presentation was consistent with ICI-induced SCLE. Nivolumab treatment was discontinued due to the severity of the rash. The rash remitted with systemic corticosteroids, high potency topical steroids, and hydroxychloroquine. Unfortunately, the patient developed intraperitoneal metastatic disease, and was enrolled in hospice care. In this paper, we highlight the importance of early identification and treatment of this irAE. A review of the literature, including a discussion on the management of ICI-induced SCLE is also provided.